2015
DOI: 10.1111/jscm.12080
|View full text |Cite
|
Sign up to set email alerts
|

Competition or Cooperation? Promoting Supplier Performance with Incentives Under Varying Conditions of Dependence

Abstract: In this study, we use the lens of social exchange theory to investigate the influence of incentives on supplier performance under various conditions of buyer–supplier dependence. We propose that incentives generally fall into two main categories: competitive, market-based incentives that reward suppliers based on how well they perform relative to other suppliers, and cooperative incentives, where both buyer and supplier share benefits based on their joint performance. Using empirical data collected from 230 buye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 93 publications
(145 reference statements)
0
116
0
4
Order By: Relevance
“…Expanding on the above, it has also been shown that such dependence can significantly affect the relationship between trust and resource allocation (Pulles et al. ), which further amplifies extant work suggesting that cooperation in such relationships can alleviate cost issues in such exchanges (Terpend and Krause ).…”
Section: Literature Review: Equity Theory and Buyer–supplier Relationmentioning
confidence: 87%
See 1 more Smart Citation
“…Expanding on the above, it has also been shown that such dependence can significantly affect the relationship between trust and resource allocation (Pulles et al. ), which further amplifies extant work suggesting that cooperation in such relationships can alleviate cost issues in such exchanges (Terpend and Krause ).…”
Section: Literature Review: Equity Theory and Buyer–supplier Relationmentioning
confidence: 87%
“…) and the power balance dynamics in the relationship can be better managed (Nyaga et al. ; Terpend and Krause ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Kraljic's four purchased-item categories, that is, strategic, leverage, noncritical, and bottleneck items, are suggested to map perfectly onto the four buyersupplier dependence matrix quadrants, that is, interdependence, buyer dominance, independence, supplier dominance, respectively (Cani€ els & Gelderman, 2007;Terpend & Krause, 2015). Our model suggested that supply managers adopt a collaborative approach to develop suppliers' sustainability-related capabilities and improve their ecological and social performance to mitigate any level of supplier sustainability risk in their interdependent relationships with suppliers.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…However, much less attention has been devoted to a theory of why and when dependent suppliers invest in R&D, which is a key determinant leading to a sustainable competitive advantage (Chen and Miller, 2007). Furthermore, little is known about the influence of social capital on the link between supplier dependence and R&D investment (Brinkhoff et al, 2015; Elking et al, 2017; Terpend and Krause, 2015). Consistent with Schildt et al (2012), we argue that organizational collaboration leads to the development of social ties and partner‐specific knowledge that affect the variance in firms’ R&D intensity.…”
Section: Introductionmentioning
confidence: 99%